Comparison of image quality and pancreatic ductal adenocarcinoma conspicuity between the low-kVp and dual-energy CT reconstructed with deep-learning image reconstruction algorithm. Issue 159 (February 2023) - Noda, Yoshifumi; Takai, Yukiko; Asano, Masashi; Yamada, Nao; Seko, Takuya; Kawai, Nobuyuki; Kaga, Tetsuro; Miyoshi, Toshiharu; Hyodo, Fuminori; Kato, Hiroki; Matsuo, Masayuki
Highlights: CT numbers of the vasculature and parenchymal organs were higher in the 40-keV imaging than in the 80-kVp imaging. The background noise was higher in 40-keV imaging than in 80-kVp imaging; however, qualitative scores were comparable in terms of the image noise and diagnostic acceptability. Virtual monoenergetic images at 40-keV showed better pancreatic ductal adenocarcinoma conspicuity than images at 80-kVp images. Abstract: Purpose: To compare the image quality and conspicuity of pancreatic ductal adenocarcinoma (PDAC) between the low-kVp and dual-energy pancreatic protocol CT reconstructed with deep-learning image reconstruction (DLIR). Method: A cohort of 111 consecutive patients (median age, 72 years; 56 men) undergoing a pancreatic protocol CT were retrospectively analyzed. Among them, 58 patients underwent 80-kVp CT (80-kVp group), and 53 patients underwent dual-energy CT and reconstructed at 40-keV (40-keV group). The medium-strength level of DLIR were used in both groups. Quantitative measurements, qualitative image quality, PDAC conspicuity, and dose-length product (DLP) were compared between the two groups using Mann–Whitney U test. Results: A total of 20 and 16 PDACs were found in the 80-kVp and 40-keV groups, respectively. CT numbers of the vasculatures and parenchymal organs ( P <.001 for all) and the background noise at both pancreatic and portal venous phases ( P <.001) were higher in the 40-keV group than in the 80-kVp group. The signal-to-noise ratio (SNR) of all anatomical structures ( P <.001–0.005), except for the liver in reviewer 2 ( P =.47), and the tumor-to-pancreas contrast-to-noise ratio (CNR; P <.001–0.01) were higher in the 40-keV group than in the 80-kVp group. No difference was found in the image quality at both phases ( P =.30–0.90). PDAC conspicuity was better in the 40-keV group than in the 80-kVp group ( P =.007–0.03). DLP at pancreatic (275 vs. 313 mGy*cm; P =.05) and portal venous phases (743 vs. 766 mGy*cm; P =.20) was comparable between the two groups. Conclusion: Under the same DLP, virtual monoenergetic images at 40-keV demonstrated higher SNR and tumor-to-pancreas CNR and better PDAC conspicuity compared to the 80-kVp setting.